Exílios voluntários: Expressões de gênero e sexualidade longe do impediemnto familiar e/ou social - Santos, Ericlis Roberto Aguiar dos; Santos, Roberta Aguiar dos; Ramos Filho, Augusto Ferreira (Cordis: Revista Eletrônica de História Social da Cidade, 2025)
This research aims to analyze how expressions of gender and sexuality are impacted by familial and/or social constraints, exploring voluntary exile as a strategy for autonomy and emancipation among LGBTQIAPN+ individuals. Based on a qualitative approach grounded in queer theory and gender and sexuality studies, semi-structured interviews were conducted with six queer individuals from different regions of Brazil. The data were analyzed using content analysis. The findings reveal that voluntary exile is often driven by the desire for freedom and identity affirmation in response to familial and societal rejection, frequently rooted in normative and religious frameworks. Participants shared that exile was the only viable path to fully and safely live their identities. This study contributes to discussions on social inclusion, mental health, and public policies, emphasizing the need for shelters, psychological support, and employment opportunities. Voluntary exile is thus understood as an act of resistance, survival, and a pursuit of dignity for the LGBTQIAPN+ population. KEYWORDS: Voluntary Exile; Gender; Sexuality; LGBTQIAPN+; Freedom.